Manipulated mesenchymal stem cell therapy in the treatment of Parkinson’s disease - Seyedeh Toktam Ekrani; Mahmoud Mahmoudi; Dariush Haghmorad; Ramiar Kamal Kheder; Alireza Hatami; Seyed-Alireza Esmaeili (Stem Cell Research & Therapy)
Abstract Mesenchymal stem cell (MSC) therapy has been considered a promising approach for the treatment of Parkinson's disease (PD) for several years. PD is a globally prevalent neurodegenerative disease characterized by the accumulation of Lewy bodies and the loss of dopaminergic neurons, leading to severe motor and non-motor complications in patients. As current treatments are unable to halt the progression of neuronal loss and dopamine degradation, MSC therapy has emerged as a highly promising strategy for PD treatment. This promise is due to MSCs' unique properties compared to other types of stem cells, including self-renewal, differentiation potential, immune privilege, secretion of neurotrophic factors, ability to improve damaged tissue, modulation of the immune system, and lack of ethical concerns. MSCs have been employed in numerous pre-clinical and clinical studies for PD treatment with promising results. However, certain aspects of their efficacy in treating PD may benefit from various genetic and epigenetic modifications. In this review article, we assess these approaches to improving MSCs for specialized treatment of PD.